A Macroeconometric Assessment of Minsky's Financial Instability Hypothesis - Matthew Greenwood-Nimmo; Artur Tarassow (Hamburg University, Department Socioeconomics, 2013)
The Financial Instability Hypothesis associated with Hyman Minsky has profound implications for the conduct of monetary policy in modern capitalist economies. At its core is the proposition that the central bank may contribute to the financial fragility of leveraged firms in its pursuit of inflation-targeting interest rate policies. This paper develops a small macroeconomic model incorporating many of the salient features of a Minskyan economy. The imposition of the resulting theoretical restrictions in a CVAR model provides support for Minsky's main proposition that interest rate innovations can drive a wedge between the cash-inflows of firms and their debt-servicing obligations. The paper concludes that the implementation of countercyclical capital requirements can provide monetary policymakers with additional policy instruments that can be used to cool overheated sectors without recourse to the `blunt instrument' of interest rate policy.
Keywords: C32; C51; E32; E52; 330; Monetary Policy; Inflation Targeting; Financial Instability Hypothesis; Cointegrating VAR; Asset Price Cycles